Europe 2020 Strategy Implementation. Grouping the Countries with the Application of Natural Breaks Method - Adam P. Balcerzak (Institute of Economic Research (IER), 2015)
In the year 2015 the European Union reaches the five year period of Europe 2020 strategy implementation. Thus, the aim of the research is to group the European countries based on the level of fulfillment aims of the strategy with the application of natural breaks method. Special consideration was given to the results of New Member States of European Union. As a result in the first part of empirical research a ranking of EU countries with application of zero unitarization method for the year 2004, 2008 and 2013 was made. Based on the rankings the countries were grouped in five classes with natural breaks method. The analysis showed that in spite of economic difficulties in Europe after global financial crisis, from the year 2004 till the year 2013 New Member States had made an important progress in the implementation of Europe 2020 strategy.
Keywords: C00; E61; O52; 330; Europe 2020 strategy; multivariate analysis; zero unitarization method; natural breaks method